Chronic traumatic encephalopathy neuropathologic change is uncommon in men who played amateur American football - Iverson, Grant L.; Jamshidi, Pouya; Fisher-Hubbard, Amanda O.; Deep-Soboslay, Amy; Hyde, Thomas M.; Kleinman, Joel E.; deJong, Joyce L.; Shepherd, Claire E.; Hazrati, Lili-Naz; Castellani, Rudolph J. (Frontiers in Neurology, 2023)
Introduction We examined postmortem brain tissue from men, over the age of 50, for chronic traumatic encephalopathy neuropathologic change (CTE-NC). We hypothesized that (i) a small percentage would have CTE-NC, (ii) those who played American football during their youth would be more likely to have CTE-NC than those who did not play contact or collision sports, and (iii) there would be no association between CTE-NC and suicide as a manner of death. Methods Brain tissue from 186 men and accompanying clinical information were obtained from the Lieber Institute for Brain Development. Manner of death was determined by a board-certified forensic pathologist. Information was obtained from next of kin telephone interviews, including medical, social, demographic, family, and psychiatric history. The 2016 and 2021 consensus definitions were used for CTE-NC. Two authors screened all cases, using liberal criteria for identifying “possible” CTE-NC, and five authors examined the 15 selected cases. Results The median age at the time of death was 65 years (interquartile range = 57–75; range = 50–96). There were 25.8% with a history of playing American football and 36.0% who had suicide as their manner of death. No case was rated as definitively having “features” of CTE-NC by all five authors. Ten cases were rated as having features of CTE-NC by three or more authors (5.4% of the sample), including 8.3% of those with a personal history of playing American football and 3.9% of those who did not play contact or collision sports. Of those with mood disorders during life, 5.5% had features of CTE-NC compared to 6.0% of those who did not have a reported mood disorder. Of those with suicide as a manner of death, 6.0% had features of CTE-NC compared to 5.0% of those who did not have suicide as a manner of death. Discussion We did not identify a single definitive case of CTE-NC, from the perspective of all raters, and only 5.4% of cases were identified as having possible features of CTE-NC by some raters. CTE-NC was very uncommon in men who played amateur American football, those with mood disorders during life, and those with suicide as a manner of death.